Meaning Identifi cation and Meaning Selection for General Language - Bergenholtz, Henning; Pedersen, Heidi Agerbo (HERMES - Journal of Language and Communication in Business, 2014)
The traditional way for lexicographers to deal with polysemy in dictionaries is by applying the terms lumping and splitting. We will not follow this tradition. Instead, we argue that the identification and selection of meaning items (= polysems) should be treated in the same way as the identification and selection of lemmas. Identifying meaning items is comparable to identifying different words, the only difference being that meaning items share the same orthographic form. When identifying meaning items, we do not at the outset assume that a somewhat abstract meaning can be split up. Instead, we always assume that there may be many meaning items connected to a lemma, and we try to identify them – though for some lemmas, it is only possible to identify one meaning item. The process of identification involves a method that combines analyzing corpora and establishing a meaning relationship to references in the world (in this contribution called things), followed by a meaning formulation of the identified meaning items which can be used for reception situations. Not always – as in the case of lemma selection – will all the identified meaning items be included in the dictionary. The selection of identifi ed meaning items will depend on the genuine purpose of the dictionary.